Safety and efficacy of elective cardioversion in atrial fibrillation the FinCV studies - Hellman, Tapio (fi=Turun yliopisto|en=University of Turku|, 2018)
Background: Major gaps exist in the evidence for predicting optimal patient outcomes of cardioversion (CV) in atrial fibrillation (AF). The aim of this dissertation was to assess the safety and efficacy of elective CV in AF. Methods: The Finnish Cardioversion study programme (FinCV) investigates the occurrence of stroke and procedural efficacy in AF patients undergoing CV. Studies included patients undergoing acute CV (FinCV), elective CV in vitamin K antagonist treated patients (FinCV2) and non-vitamin K antagonist treated patients (Fin-CV3). The patients' data were retrospectively collected during the 2003–2016 timeframe from nine Finnish hospitals. Altogether, the FinCV studies comprised 5441 patients and 10852 CVs, of which the FinCV2 study encompassed 1342 patients with 1998 elective CVs. Results: Elective CV was unsuccessful or AF recurred within the 30-day follow-up after an initially successful CV in 42.6% (FinCV2). Altogether, 6 (0.4%) cerebral thromboembolisms were detected within follow-up and patients with low (2.0–2.4) therapeutic internationalized normalized ratios (INRs) at the time of elective CV had a higher risk for thromboembolic events than patients with high (≥2.5) therapeutic INRs (0.9% vs. 0.1%, p=0.03) (FinCV2). In the combined registry of the FinCV studies the primary composite end-point was designated as an occurrence of death, thromboembolism, unsuccessful CV, recurrence of AF or acute arrhythmic complication within follow-up. The composite adverse outcome was observed after 1669 (38.4%) CVs and patients with AF episodes lasting 24–48 hours had the lowest risk of adverse outcomes. Conclusions: The intensity of anticoagulation in elective CV of AF is associated with the risk of postprocedural thromboembolisms. Nevertheless, CV in AF has relatively few safety issues, although more room exists for improvement in efficacy outcomes of CV in contemporary medicine.

Eteisvärinän elektiivisen kardioversion turvallisuus ja tehokkuus – Fincv-tutkimukset Tausta: Vaikka rytminsiirto on keskeisin toimenpide eteisvärinän palauttamisessa sinusrytmiin, tehokkaan rytminsiirron ennustetekijöistä on vain vähän tietoa. Tämä väitöskirja selvittää eteisvärinän elektiivisen kardioversion turvallisuuden ja tehokkuuden ennustetekijöitä. Menetelmät: FinCV-tutkimukset ovat osa retrospektiivistä rekisteritutkimusohjelmaa, jossa selvitetään eteisvärinän kardioversioon liittyvää aivoinfarkti- ja verenvuotoriskiä. Potilasaineisto kerättiin vuosien 2003 – 2016 aikana yhdeksästä suomalaisestsa sairaalasta. Tutkimukset sisältävät yhteensä 5441 potilasta ja 10852 kardioversiota, joista FinCV2-tutkimukseen kuuluu 1342 potilasta ja 1998 elektiivistä kardioversiota. Tulokset: FinCV-tutkimuksien yhdistelmäaineistossa ensisijainen yhdistelmäpäätetapahtuma,johon sisältyi rytminsiirron epäonnistuminen, eteisvärinän uusiutuminen tai akuutti rytmihäiriökomplikaatio, verenkiertohäiriön ilmaantuminen tai kuolema 30 päivän seuranta-ajan sisällä, ilmeni 1669 (38.4 %) rytminsiirrossa. Potilailla, joiden eteisvärinäkohtauksen kesto oli 24 – 48 tuntia, oli kaikkein vähiten haittatapahtumia. Toisaalta elektiivinen rytminsiirto epäonnistui tai eteisvärinä uusiutui 30 päivän seurantaajan kuluessa 42.6 % toimenpiteistä. Aivoverenkiertohäiriöitä todettiin vähän 0.4 % FinCV2-tutkimusaineistossa 30 päivän seuranta-ajan kuluessa ja niillä potilailla, joilla rytminsiirtohetkellä INR-arvo oli 2.0 – 2.4, oli korkeampi aivoverenkiertohäiriöriski kuin potilailla, joiden INR-arvo oli ≥ 2.5 rytminsiirtohetkellä (5/529 (0.9 %) vs. 1/895 (0.1 %), p = 0.03).